2020
DOI: 10.1186/s12935-020-01563-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of let-7b-5p contributes to an anti-tumorigenic macrophage phenotype through the SOCS1/STAT pathway in prostate cancer

Abstract: Background Dysfunction of microRNAs (miRNAs) is a major cause of aberrant expression of inflammatory cytokines and contributes to macrophage polarization. Proinflammatory M1 macrophages promote T helper (Th) 1 responses and show tumoricidal activity, whereas M2 macrophages display regulatory functions in tissue repair and remodeling and promote Th2 immune responses. Previous studies have shown that miRNA let-7 is associated with cellular differentiation and that the expression of let-7b-5p is significantly aug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…Simultaneously, SOCS1 contains the SH2 (Src Homology 2) functional domain, which can inhibit STAT1 activity ( 39 ). The SOCS1/STAT1 pathway played a critical role in inhibiting the growth of prostate cancer by regulating macrophage polarization in the tumor microenvironment ( 40 ). Liang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, SOCS1 contains the SH2 (Src Homology 2) functional domain, which can inhibit STAT1 activity ( 39 ). The SOCS1/STAT1 pathway played a critical role in inhibiting the growth of prostate cancer by regulating macrophage polarization in the tumor microenvironment ( 40 ). Liang et al.…”
Section: Discussionmentioning
confidence: 99%
“…S14). let-7b-5p and miR-24-3p are associated with the JAK-STAT signaling pathway to induce M2 macrophage polarization ( 40 , 41 ). In the presence of the let-7b-5p and miR-24-3p inhibitors, M1-M2 macrophage polarization of DS-EXO–treated RAW264.7 cells (LPS + and IFN-γ + ) was inhibited ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al found that downregulation of miR-21 by ailanthone reduced the proliferative potential of VS cells and induced apoptosis and autophagy (89). Other deregulated miRNAs also serve as modulators of tumor-related signaling pathways, such as miR-340 in Ras/Raf/MAPK (138) and let-7b in SOCS1/STAT (139). Notably, the contributions of miR-19, miR-21 and miR-221 to tumor growth are all related to their down-regulation of tumor suppressor PTEN (36,136,140), suggesting the role of PTEN and its downstream PI3K/Akt/mTOR signaling pathway in VS cancerigenic process.…”
Section: Mirnasmentioning
confidence: 99%